Implementasi Sistem Otomasi Perpustakaan Berbasis Slims 7 Cendana Dengan Pemanfaatan Barcode Di Perpustakaan Universitas Dirgantara Marsekal Suryadarma - Sutarno; Muryan Awaludin (Fakultas Ilmu Komputer & Desain, 2024)
Information Technology is one technology that is developing rapidly at this time. With the advancement of information technology, access to available data or information can take place quickly, efficiently and accurately. The development of C is driving the development of information technology-based administration systems. It also penetrated into university management, including one in the management of the library system. Increasing the professionalism and quality of education and services offered by an educational institution is one of the attractions of public interest as one of the criteria in choosing an educational institution. A library is a place, a building that is provided for the maintenance and use of a collection of books and so on can also be interpreted as a collection of books, magazines, and other library materials that are stored to be read, studied, discussed (Depdikbud, 1996). Management of libraries today increasingly demands quality and professionalism so that the results can be utilized to the maximum extent possible by its users. With the current technological developments, an information system that handles library administration is indeed needed. The information system is related to book data management, member data management, book loan circulation data management and other administrative data management. With the existence of the library information system, it can certainly improve the effectiveness of library use.